Designing a Qualitative Research Proposal or Project - Aguilar, Jorge (CIEX JOURNAL, 2017)
This workshop is intended for bachelor’s and master’s students who need to design a qualitative research project or proposal. The workshop will briefly look at the essential components and processes of qualitative research. Through practical tasks done individually and in small groups and the discussion of specific examples of qualitative research studies, participants will be encouraged to critically reflect on and gain a deeper understanding of the qualitative research process. Attendees will be involved in planning a qualitative study by doing a sequence of tasks, which aim to help them end up with a tentative research project or proposal.